How to Increase The Purchase of Local Fashion Brand on E-Commerce Platforms? - Ratnasari, Ina; Muarif, Muhammad Akmal; Arnu, Anggi Pasca; Hannie, Hannie (Universitas Bangka Belitung, 2024)
Progress of the fashion industry is growing very rapidly in the national industry. Erigo is one of the local fashion brands that are in demand by the public. Increasing of the fashion industry is matched by the progress of the digital world. Shopee is one of the e-commerce platforms that provides a special space for local fashion brands. This research uses quantitative methods with descriptive and verifiative approaches. The population in this study was the followers of the Shopee Erigo account using the Taro Yamane formula to determine the number of samples and found the results of 400 respondents. The sampling method used in this study was purposive sampling. This study used scale range analysis techniques and Partial Least Square Regression with tools by Smart PLS 4.0 software data. The results of this study showed a partial influence of Social Media Branding by 21.4%, Shopping Lifestyle by 56.5%, Fashion Involvement by 16.4% on Purchasing Decisions. The simultaneous influence of Social Media Branding, Shopping Lifestyle, Fashion Involvement on Purchasing Decisions has a value of 75.2% which is classified into the category of strong influence and 24.8% influenced by other factors that were not examined in this study.